Analisis Kondisi Fisik Tim Ekstrakulikuler Sepak Bola SMA Negeri Balung: Studi Berdasarkan Posisi Pemain di Lapangan - Feri, Maulana Makrus; Hardovi, Bahtiar Hari; Apriliyanto, Rizki (Universitas Hamzanwadi, 2025)
This study aims to analyze the physical condition of Balung State High School football players based on playing position. This study uses a quantitative descriptive method by measuring two main indicators, namely endurance and strength. The population of this study were all members of the Balung State High School soccer extracurricular team totaling 16 people, consisting of 3 students positioned as goalkeepers, 4 as defenders, 3 as midfielders, and 6 as strikers. Data were collected through physical tests using the fartlek training method for endurance and squat test for strength, then statistically analyzed to compare the physical condition of each position, namely goalkeeper, defender, midfielder, and striker. The results showed that the majority of players were 17 years old (37.5%), while 25% of players were 19 years old. In terms of physical condition, Satriyo (striker) has the highest endurance and strength with a percentage of 8.92%. Meanwhile, Tegar (goalkeeper) has the lowest score of 2.12%. The striker position has the largest number of players compared to other positions. Overall, the majority of players have a fairly good physical condition with a range of 6.77%-7.93%. It was concluded that there were significant variations in the physical condition of players based on their position on the pitch. The two main components analyzed, endurance and strength, showed different results between individuals and positions.